Conceptual approaches of the rural space - Talida Giambaşu; Ioan Nicolae Alecu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
This paper is a bibliographic study of the rural space concept, from its establishment and until now. In this respect, the following works from the dedicated literature have been studied: scientific works, doctoral dissertations, case studies, books and websites dedicated to this topic. The used method was the bibliographic research and the synthesis of conceptual approaches in own manner. The conclusions that may be drawn from the performed research reveal certain concept dynamics in time, as the functions and services of the rural space were better understood, leading to the conceptual development of the rural space. Also, the approach of the development of the rural-urban dichotomy has outlined the rural space concept more clearly.
Keywords: 330; concept; dichotomy; rural space